Hepatic Regenerative Potential of Mouse Bone Marrow Very Small Embryonic‐Like Stem Cells. Issue 8 (August 2015) - Chen, Zhi‐Hua; Lv, Xin; Dai, Haiyan; Liu, Changlong; Lou, Debao; Chen, Ruoping; Zou, Gang‐Ming
<x xml:space="preserve">Abstract</x> Very small embryonic‐like stem cells (VSELs) are a Sca‐1 + Lin‐CD45‐ cell population that has been isolated from the bone marrow of mice. The similarities and differences between the mRNA profiles of VSELs and embryonic stem (ES) cells have not yet been defined. Here, we report the whole genome gene expression profile of VSELs and ES cells. We analyzed the global gene expression of VSELs and compared it with ES cells by microarray analysis. We observed that 9, 521 genes are expressed in both VSELs and ES cells, 1, 159 genes are expressed uniquely in VSELs, and 420 genes are expressed uniquely in ES cells. We found that although VSELs are similar to ES cells in their expression of genes associated with stem cell behavior and pluripotency, there are also differences in their mRNA expression. We further analyzed the expression of stem cell‐associated genes in VSELs and ES cells, and found that there were differences in these genes. For instance, the Pkd2 and Yap1 gene were reduced in their expression in VSELs when compared with ES cells. But we also found Zfp54 gene expression was higher in VSELs compared with ES cells. More interestingly, we demonstrated that VSELs express c‐kit, the stem cell factor (SCF) receptor. In vitro, SCF promoted VSEL differentiation into hepatic colonies in the presence of hepatocyte growth factor. In vivo, transplantation of VSELs directly into CCl4‐induced injured livers significantly reduced serum ALT and AST levels. Therefore, these data suggest that VSELs play a role in the repair of injured livers. J. Cell. Physiol. 230: 1852–1861, 2015. © 2014 Wiley Periodicals, Inc.